ANALYSIS OF EMPLOYMENT AND UNEMPLOYMENT IN MUNICIPALITIES OF GEORGIA - Kvirkvaia, Murtaz (European Scientific Journal, ESJ, 2016)
The article includes detailed employment and uniploymant analysis in each municipality. In the analysis we use results from household survey conducted by the National Statistics Service. More specific information about the labour market at the municipal level was collected through cooperation with local municipalities. For the analysis we used information from municipalities’ web pages, telephone conversations with stakeholders, personal meetings with experts and so on. It should also be noted that a certain part of the data obtained from municipalities and from administrative territorial units have an approximate nature, but based on these information it is possible to gain some valuable conclusions and make assumptions. Terms and reality of employment analysis is carried out not only at the level of the municipality but on the country and regional ones as well.